Pharmacodynamic studies of antimalarial drugs in a murine malaria model - Moore, Brioni R. (Curtin University, 2011)
Murine malaria models have proved to be a valuable preclinical tool, particularly in the development of new concepts in the research of human malaria. Plasmodium berghei (P. berghei), is the most extensively studied and manipulated rodent parasite and as a laboratory model, is largely selected for studies relating to developmental biology of parasites and investigation into new and innovative drug therapies. Whilst direct extrapolation from rodent biology to human malarias should be generally avoided, murine malaria models may contribute a greater understanding of important characteristics for antimalarial drug development and drug efficacy studies. However, there is currently a paucity of murine pharmacological data available for both commonly used, and emerging, antimalarial therapies. The findings of the studies in this thesis are seen as an important contribution to the preclinical knowledge of the investigated drugs which to date, have not been adequately studied.The aim of the thesis was to investigate the efficacy, pharmacokinetic and/or pharmacodynamic properties of various antimalarial drugs, in a P. berghei murine malaria model. Specific aims were to: (i) Evaluate the pharmacodynamic effects of dihydroartemisinin (DHA) in asplenic P. berghei infected mice. (ii) Investigate the pharmacokinetic and pharmacodynamic properties of single dose piperaquine (PQ) in healthy and P. berghei infected mice. (iii) Investigate the extended antimalarial effect of PQ concentrating on drug efficacy, re-inoculation outcomes and parasite viability. (iv) Evaluate the pharmacokinetic and pharmacodynamic properties of single and multiple doses of chloroquine (CQ) in healthy and P. berghei infected mice.Using an asplenic model of P. berghei malaria, the efficacy of single doses of DHA (0, 10, 30 and 100 mg/kg) were evaluated in uninfected and P. berghei infected, intact and asplenic mice. Haematology, liver biochemistry and histopathology were performed to investigate the responses of key organs to malaria infection. Whilst overall efficacy of single dose DHA in asplenic mice was shown to be similar to intact mice, the rate of parasite recrudescence after parasite nadir (20 h at all doses studied) was significantly higher in the asplenic mice, particularly at higher doses (30 and 100 mg/kg DHA). Histopathology of the liver and associated blood chemistries, demonstrated an increased stimulation of liver function during malaria infection in asplenic mice, when compared to intact mice.Whilst studying the pharmacokinetic and pharmacodynamic responses of PQ in the P. berghei malaria treatment model, particular focus was placed on (i) pharmacodynamic properties of single doses of PQ (0, 10, 30 and 90 mg/kg PQ phosphate (PQP)); (ii) pharmacokinetic parameters of PQ in healthy and P. berghei infected mice; (iii) efficacy of combined doses of 10 mg/kg PQP and 30 mg/kg DHA. Single dose administration of PQP resulted in a median survival time of 4, 10 and 54 days after doses of 0, 10 and 30 mg/kg PQP, respectively, while mice receiving a single 90 mg/kg dose showed a medium survival time exceeding 60 days (experimental endpoint). Pharmacokinetic analysis determined the elimination half-life of PQ in healthy and P. berghei infected mice was 18 and 16 days, respectively. Furthermore, extrapolation of PQ concentrations suggested that at 60 days the plasma drug concentration would be ineffective at suppressing the P. berghei infection (<10 μg/L). Combination of PQP and DHA resulted in a significantly lower parasite nadir (22 ± 12 fold) than for either drug given individually.Given that high dose PQP (90 mg/kg) demonstrated extended antimalarial efficacy, further invetsigations were pursued on drug efficacy, re-inoculation outcomes and parasite viability after a single 90 mg/kg dose of PQP. Investigation showed that after initial dosing, PQ concentrations were not adequate to suppress parasitaemia after 25 days. Furthermore, although viable parasites were present up to 90 days after drug administration, once these viable parasites were passaged into naive mice they were found to be generally resistant to PQ when exposed to the drug for a second time. Overall, PQ was found to have a substantial antimalarial effect in this model with this effect appearing to be sufficient for a host immunological response to be established thus resulting in the long term survival of P. berghei infected mice.Although CQ is widely used in preclinical animal studies, there is a paucity of comprehensive pharmacokinetic data of CQ in animal models. In this thesis robust pharmacokinetic and pharmacodynamic data of CQ is presentated after single and multiple dose administration of CQ in the P. berghei malaria model. The pharmacokinetics of desethyl-CQ (DECQ), the major active metabolite of CQ, were estimated. Pharmacodynamic data demonstrated that parasite nadir was reached 79 h after a single dose of 60 mg/kg CQ, with all mice developing parasite recrudescence. Multiple dose (5 x 50 mg/kg CQ; dosed every 24 h) administration resulted in parasitaemia falling below the limit of detection. Despite a short period of recrudescence (between 10 and 24 days after initial dose), parasitaemia remained undetectable until the experimental end point (35 days after the initial dose). Pharmacokinetic analysis determined an elimination half-life of 46.6 h in healthy mice and 99.3 h in malaria-infected mice (single dose data; non-compartmental analysis). The mean rate of formation of DCQ from CQ was 0.63 ± 0.55 h-1 with a formation half-life of 1.7 ± 1.0 h.Consequently, the drug efficacy, pharmacodynamic and pharmacokinetic data included in this thesis demonstrates that the current P. berghei murine malaria treatment model can be used as a valuable preclinical conceptual tool for the investigation of antimalarial drugs such as DHA, PQ and CQ.